Age Estimation via Orocraniofacial Based on Direct Observation and Radiography - Asdiana, Andi Eka; Puspitawati, Ria; Soedarsono, Nurtami (Journal La Medihealtico, 2024)
Determining the estimated age in forensics is very important because it involves legal accountability. The method of determining age estimation can be done by direct measurement of the orocraniofacial bone or by using radiography. This article examines theseveral studies as well as parameters for determining age estimation using orocraniofacial. Search for published articles on Elsevier, Pubmed, Google Scholar, Research Gate, and NCBIon range2007-2021 years. The results show that it is more advisable to determine the age estimate by direct measurement compared to using radiography because it is prone to distortion.